x 1 2 0 1 6 + x 2 2 0 1 6 + ⋯ + x 2 0 1 6 2 0 1 6
If x 1 , x 2 , … , x 2 0 1 6 are the roots of the equation x 2 0 1 6 − 2 0 1 6 x − 2 = 0 , then find the value of the expression above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x 2 0 1 6 − 2 0 1 6 x − 2 x 2 0 1 6 ∑ x 2 0 1 6 = 0 = 2 0 1 6 x + 2 = ∑ ( 2 0 1 6 x + 2 ) = 2 0 1 6 ∑ x + ∑ 2 = 2 0 1 6 ( 0 ) + 2 0 1 6 ⋅ 2 = 4 0 3 2
This solution is similar to mine.
Some other solution... By Newton's sums
x 1 2 0 1 6 + x 2 2 0 1 6 + … + x 2 0 1 6 2 0 1 6 = S 2 0 1 6
S 2 0 1 6 + S 2 0 1 5 ⋅ a 1 + … + S 1 ⋅ a 2 0 1 5 + 2 0 1 6 ⋅ a 2 0 1 6 = 0
Since a 1 , a 2 , a 3 , . . . a 2 0 1 4 = 0 and S 1 = − a 1 = 0 , then
S 2 0 1 6 + S 2 0 1 5 ⋅ 0 + … + 0 ⋅ a 2 0 1 5 + 2 0 1 6 ⋅ a 2 0 1 6 = 0
S 2 0 1 6 + 2 0 1 6 ⋅ a 2 0 1 6 = 0
S 2 0 1 6 + 2 0 1 6 ⋅ ( − 2 ) = 0
S 2 0 1 6 = 4 0 3 2
Problem Loading...
Note Loading...
Set Loading...
x 2 0 1 6 − 2 0 1 6 x − 2 = 0
x 2 0 1 6 = 2 0 1 6 x + 2 . . . . ( 1 )
Putting x = x 1 , x 2 , . . . . . , x 2 0 1 6 in ( 1 ) repeatedly, and add them, we get
x 1 2 0 1 6 + x 2 2 0 1 6 + . . . . . . . . + x 2 0 1 6 2 0 1 6 = 2 0 1 6 ( x 1 + x 2 + . . . . . + x 2 0 1 6 ) + 4 0 3 2
Using Vieta, x 1 + x 2 + . . . . + x 2 0 1 6 = 0
So the value of expression is x 1 2 0 1 6 + x 2 2 0 1 6 + . . . . . . . . + x 2 0 1 6 2 0 1 6 = 4 0 3 2